The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10456-014-9439-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of vasculogenesis in 3D fibrin matrices mediated by the interaction of adipose-derived stem cells and endothelial cells

Abstract: Vascularization of tissue-engineered constructs is essential to provide sufficient nutrient supply and hemostasis after implantation into target sites. Co-cultures of adipose-derived stem cells (ASC) with outgrowth endothelial cells (OEC) in fibrin gels were shown to provide an effective possibility to induce vasculogenesis in vitro. However, the mechanisms of the interaction between these two cell types remain unclear so far. The aim of this study was to evaluate differences of direct and indirect stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 40 publications
7
133
1
1
Order By: Relevance
“…AD-MSCs produce and secrete many angiogenic factors, such as VEGF (Lauvrud et al, 2016) and HGF (Suga et al, 2009 (Verseijden et al, 2010). ADMSCs can produce growth factors and cytokines such as HGF, TNF-alpha (Kachgal and Putnam, 2011), PD-ECGF, FGF-2, MMP-9, Ang-2, pentraxin-3 (Rohringer et al, 2014), collagen IV, and fibronectin (MerfeldClauss et al, 2010). AD-MSCs have also been shown to have a high proliferative potential than BM-MSCs (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…AD-MSCs produce and secrete many angiogenic factors, such as VEGF (Lauvrud et al, 2016) and HGF (Suga et al, 2009 (Verseijden et al, 2010). ADMSCs can produce growth factors and cytokines such as HGF, TNF-alpha (Kachgal and Putnam, 2011), PD-ECGF, FGF-2, MMP-9, Ang-2, pentraxin-3 (Rohringer et al, 2014), collagen IV, and fibronectin (MerfeldClauss et al, 2010). AD-MSCs have also been shown to have a high proliferative potential than BM-MSCs (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ADSCs appear to be key regulators of new blood vessel formation and have been demonstrated to differentiate easily to endothelial cells and to form quickly and simply vessel-like structures in Matrigel® substrates with assumed endothelial function [40]. Moreover, in different studies, regarding for instance cardiac infarct treatment, epithelial regeneration or neural tissue healing, vessel formation has been observed after injection of ADSCs alone or in the combination with other cell types [61,62]. …”
Section: Mesodermal Potential Of Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
“…Moreover, based on recent studies, the endothelialization of ASC-TEVS could have a beneficial side effect since ASC have been shown to differentiate along a smooth muscle lineage pathway upon EC contact [16,20]. This means that ASC-TEVS endothelialization could induce a myogenic differentiation of ASC located directly under the endothelium leading to the formation of a media-like layer.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have confirmed the adipose-derived stromal cells (ASC) potential for multilineage differentiation as well as their low immunogenicity [15][16][17][18][19]. More recently, ASC have also been investigated in the context of vascular tissue engineering [16,[20][21][22]. Indeed, given ASC's differentiation capabilities, they were evaluated both as an EC source to form an endothelium-like monolayer in grafts lumen; or as a SMC source to seed vascular scaffolds.…”
Section: Introductionmentioning
confidence: 95%